“Evaluación del comportamiento agronómico de tres variedades de zanahoria (Daucus carota), sembradas en varios sustratos orgánicos y suelos agrícolas en la zona de Pimocha” - Manzaba Cali, Diana Nohely (2018)
VII. SUMMARY This research was conducted in the hacienda "Will of God" owned by Mr. Pedro Enrique Gómez Velásquez, located at Km 5.0 of the road Baba Babahoyo, Los Rios province with geographical coordinates of -1.771800 latitude, and -79.586061 length. The experimental area has a height of 7 masl, presents a humid tropical climate, with an average annual temperature of 25.7 ° C, an average annual precipitation of 1845 mm, relative humidity of 76% and 804.7 hours of average annual heliophilous. Seeds of the varieties Ravanello Candela Digniaccio, Carota Kuroda and Carota Berlicum 2 were used as seeding material. The objectives were to study the agronomic behavior of three carrot varieties; identify the most appropriate type of organic soil substrate to improve crop production and economically analyze the treatments under study. The treatments and sub-treatments were made up of carrot varieties and types of substrates such as 50 kg of common soil; 40 of common land + 35 kg of farm land; 50 kg of common soil +12 kg of cow dung; 40 of farm land + 8 algasoil; 50 kg of common land + 5 kg of ash and 40 of farm land. The experimental design used was Divided plots, with three treatments, six sub-treatments and three repetitions. For the comparison and adjustments of means of treatments, the Tukey test was used. For the management of the trial, soil preparation, sowing, irrigation, weed control, fertilization, phytosanitary control and harvesting were carried out. From the results it was determined that the highest plant height 40 days reported to the variety Ravanello Candela Digniaccio, using as substrate 50 kg of common ground +12 kg of cow dung, while the crop height plant excelled with the same variety but with the substrate based on 40 of farm land + 8 algasoil; the carrot variety Ravanello Candela Digniaccio, applying the substrate with 50 kg of common soil recorded higher averages in the variables length and diameter of the fruit; fruit weight obtained averages above the variety carota Berlicum 2 using as substrate 40 common ground + 35 kg of land estate and increased crop yield was presented with the choice carota Kuroda and as a means of substrate 50 kg of ground common , unlike the economic analysis, whose highest net benefit was observed in the variety Carota Berlicum 2 with the substrate type of 50 kg of common land with $ 61.18. Keywords: Carrot (Daucus carota), Organic substrates, Agricultural soils, Common land, Farm land; Cow dung; Algasoil; Common Earth, Ash.